Avaliação de cultivares de feijão caupi (Vigna unguiculata (L.) WALP) no município de Humaitá - AM - Schutz Junior, Germano (Brasil, 2021)
Cowpea is a rustic crop with good productivity in low fertility soils. Due to the high protein content it becomes a great food source for low income families. This legume can be intercropped with other crops such as maize (Zea mays L.) and cassava (Manihot esculenta Krantz), and can be grown in both lowland and firm land. The present work aimed to evaluate 6 (six) cowpea cultivars (BRS Tucumaque, BRS Cauamé, BRS Milenio, BRS Rouxinol, BRS Paraguaçu, BRS Caldeirão) and two regional Creole varieties, from the Butter subclass and Vinagre subclass, in the municipality. of Humaitá - AM. The design was a randomized block with the characteristics evaluated: Final Stand, Flowering, Dry Mass of Shoot, Number of Leaves per Plant, Laying, Length of Main Branch, Number of Nodes of Main Branch, Number of Side Branches, Height of Plant, Final Plant Population, Number of Pods per Plant, Number of Grains per Pod, Weight 1,000 Grains, Productivity. For all factors, the cultivar BRS Paraguaçu was the one that presented the most satisfactory index for its production in the region, but the work must be repeated to revalidate the data.